Penatalaksanaan Holistik Pasien Wanita Usia 16 Tahun Dengan Diabetes Melitus Tipe I - Larasati Anindiya Basica; Sahab Sibuea (CV. Jasa Sukses Abadi, 2021)
Diabetes melitus type 1 (DM type 1) is a serious problem because it’s a chronic disease that last a lifetime. This type of diabetes can only be controlled but can’t be cured. Patients with diabetes melitus type 1 must continue to use insulin for life so it’s called as an insulin-dependent diabetes melitus. To Identify clinical problems owned by patient to improve patient’s quality of life as well as prevent complications and toatient holistically and comprehensively according to the problems were found in patient, and managing based on Evidence Based Medicine with a patient-centered approach and family approach. This study is a case report. Primary data werw obtained through history taking, physical examination and home visits. Secondary data were obtained from the patient's medical record. Assessment was based on a holistic diagnosis from the beginning, process, and the end of study qualitatively. Ms.K, 16 years old, has been diagnosed diabetes melitus type 1, with concerns that her complaints will increase and not improve. Limited knowledge of the patient's health condition in the form of life style, physical activities, dietary habit and lack of motivation and family encouragement to bring patients to control their health regularly are factors that cause problems that occur in patients and family. Education of Ms.K problems has been done by providing counseling to improve the patient's family knowledge.